1974
DOI: 10.1073/pnas.71.11.4579
|View full text |Cite
|
Sign up to set email alerts
|

Viable Molecular Hybrids of Bacteriophage Lambda and Eukaryotic DNA

Abstract: A bacteriophage X strain has been constructed and a method developed by which DNA from potentially any source can be covalently inserted through EcoRI cohesive ends into the middle of the X DNA. These hybrid DNAs can infect nonrestricting Escherichia coli cells and can then propagate as plaque-forming phage. A unique feature of this X strain is that extra DNA in the middle of its genome is required for plaque formation. A large number of such phages have been produced with E. coli DNA and Drosophila melanogast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(61 citation statements)
references
References 10 publications
3
57
0
1
Order By: Relevance
“…By hybridization, radioactive 6S RNA was found to be complementary to EcoRI fragment no. 3, the subterminal fragment from the right-hand half of the lambda chromosome (17,18), and to fragments Hind-2 and Hae-10 ( Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…By hybridization, radioactive 6S RNA was found to be complementary to EcoRI fragment no. 3, the subterminal fragment from the right-hand half of the lambda chromosome (17,18), and to fragments Hind-2 and Hae-10 ( Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Attaching the Drosophila DNA to the pSC101 plasmid enabled Hogness and his coworkers to confirm in late 1974 the cloning of eukaryotic cell genes in bacteria and to use DNA cloning to map sequences in Drosophila chromosomes (63). Concurrently, other laboratories focused on constructing new bacteriophage λ variants able to produce viable molecular hybrids (64,65), and, in November 1974, Ron Davis and his coworkers at Stanford reported that such hybrids can be propagated as plaque-forming phage (66).…”
Section: Gordon Conference Discussion About Biohazard Concerns and Cmentioning
confidence: 99%
“…Ironically with regard to Pollack's scenario, Mertz's 1975 PhD dissertation (67) stated that "scientific problems have been encountered during attempts to use λdvgal as a vector for replicating other DNA molecules" and that "the plasmid is unstable and readily lost from its E. coli host" (67). It was later learned that insertion of foreign DNA into the λdvgal site that the Berg team had used for construction of hybrid DNA molecules (52, 54) disrupts a gene essential for λdvgal replication in bacteria (54,66,69), possibly explaining the lack of success of the DNA cloning attempts reported in Mertz's dissertation (67). But Pollack's concerns and Berg's decision had importantly raised awareness about possible biohazardous consequences of creating novel DNA combinations (54).…”
Section: Biohazard Speculations Mountmentioning
confidence: 99%
“…E. coli JMI05 f1lacpro, thi, strA, endA, sbcB15, hsdR4 (F', traD36, proAB, lacIQ, lacZf1M15) was purchased from Amersham Co. E. coli C600 r k -,m k -, F-, thi1, thr1, leuB6, lacY1, tonA21, supE44, A-was obtained from R. Davis. 9 ) Plasmids pBD64,t°) pUBl10 ll ) and pBR322 12 ) were used as vectors.…”
Section: Methodsmentioning
confidence: 99%